The Performance of Health Workers in Ethiopia : Results from Qualitative Research - Lindelow, Magnus; Serneels, Pieter; Lemma, Teigist (World Bank, Washington, DC, 2012)
Insufficient attention has been paid to understanding what determines the performance of health workers and how they make labor market choices. This paper reports on findings from focus group discussions with both health workers and users of health services in Ethiopia, a country with some of the poorest health outcomes in the world. It describes performance problems identified by both health, users and health workers participating in the focus group discussions, including absenteeism and shirking, pilfering drugs and materials, informal health care provision and illicit charging, and corruption. The second part of the paper presents four structural reasons why these problems arise: (1) the ongoing transition from a health sector dominated by the public sector, toward a more mixed model; (2) the failure of government policies to keep pace with the transition toward a mixed model of service delivery; (3) weak accountability mechanisms and the erosion of professional norms in the health sector; and (4) the impact of HIV/AIDS. The discussions underline the need to base policies on a micro-analysis of how health workers make constrained choices, both in their career and in their day to day professional activities.